Geographical Education and field trips as a teaching strategy: a comparative study from the Iberoamerican Geoforo - Sousa Fernandes, Silvia Aparecida [UNESP]; Garcia Monteagudo, Diego; Souto Gonzalez, Xose M. (Univ Barcelona, Servei Publicacions, 2016)
Field trips make up some of the main teaching strategies and teaching methods used by teachers from different academic disciplines. In geography, many academic publications and teaching experiences have been reported in scientific events, articles and books. In this paper is a study of how field trips or study visits have been published in the geographical education in the IberoAmerican countries, especially in studies performed in Brazil and Spain. The object we want to address in this study is the basic core Forum 21, held at the Iberoamerican Geoforo, launched in February 2015. In the field trips and empirical academic research resource and as a teaching strategy were discussed. Therefore we intend to evaluate the different contributions and explain their theoretical context with the objective of developing a synthesis of the debate and move a critical reflection on study visits in their methodological, didactic and their relationships with the school curriculum aspects.
Keywords: Geoforo; field trips; teaching methods; teaching Geography